2007
DOI: 10.1102/1470-7330.2007.0006
|View full text |Cite
|
Sign up to set email alerts
|

Optical mammography: a new technique for visualizing breast lesions in women presenting non palpable BIRADS 4-5 imaging findings: preliminary results with radiologic-pathologic correlation

Abstract: The purpose of this prospective study is to determine the diagnostic accuracy of near-infrared breast optical absorption imaging in patients with Breast Imaging Reporting and Data System (BIRADS) 45 non-palpable lesions scheduled for biopsy, using pathology after core or excisional biopsy as a reference. The patient's breast was positioned onto a panel of red light-emitting diodes (640 nm). A soft membrane was inflated to exert a uniform pressure on the breast. Transmitted light was detected using a CCD camera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Because of the poor spatial resolution caused by intense light scattering in soft tissues, optical tomography alone has not been widely used in clinical studies. With the improvements in technology and mathematical techniques, DOT combined with other imaging techniques such as US [2][3][4], X-mammography [5] or MRI [6,7] shows promise in overcoming these problems and has generated considerable interest. The aim of our study was to investigate prospectively the feasibility of combining US with DOT in differentiating breast lesions and to evaluate its clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the poor spatial resolution caused by intense light scattering in soft tissues, optical tomography alone has not been widely used in clinical studies. With the improvements in technology and mathematical techniques, DOT combined with other imaging techniques such as US [2][3][4], X-mammography [5] or MRI [6,7] shows promise in overcoming these problems and has generated considerable interest. The aim of our study was to investigate prospectively the feasibility of combining US with DOT in differentiating breast lesions and to evaluate its clinical efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating viscoelastic tissue modelling in NIRS is an approach that has seen some recent activity. Dynamic measurements induced by changes in pressure applied to the tissue can provide a rich dataset for robust, often ratiometric, interpretation of oxygen saturation and total haemoglobin values [106][107][108][109][110][111]. These mechanical models are almost uniformly applied in post-processing or forward modelling [112], owing to the complexity of solving the viscoelastic problem in irregular domains.…”
Section: Prior Information: Biophysical Models (A) Biophysical Modelsmentioning
confidence: 99%
“…Some evidence has been found that malignant breast tumours have lower electrical impedance than surrounding normal tissues (Malich et al, 2001;Prasad et al, 2008). This observation has led to the proposal that electrical impedance could be used as an indicator for breast cancer detection (Cherepenin et al, 2001;Cherepenin et al, 2002;Athanasiou et al, 2007).…”
Section: Electrical Impedance Tomography As a Primary Screening Technmentioning
confidence: 99%